1997
DOI: 10.5144/0256-4947.1997.53
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in the Eastern Region of Saudi Arabia: A Population-Based Study (1987-1988)

Abstract: This study presents the findings of the first population-based tumor registry in the Eastern region (ER). Data on all cancer sites, in 1987 and 1988, were captured from all health facilities in the ER. A regional population census was obtained from regional health authorities. Cancer deaths were obtained from death registries. Age-specific rate, crude incidence rate (CIR), age-standardized incidence rate (ASR) and relative age-standardized incidence rate (%ASR) were compared with available population-based dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…In Riyadh, two-thirds of BC cases were premenopausal [33][34]. As well as result was consistent since the first registry in the eastern province for Saudi women [35] which mentioned that the crude incidence rate (CIR), age-standardized incidence rate (ASR) were 43.6 and 95.5, correspondingly. In another study in eastern region between 1985-1995, they also found that most of the females were pre-menopausal (79%) at age below 50 years [15].…”
Section: Discussionsupporting
confidence: 50%
“…In Riyadh, two-thirds of BC cases were premenopausal [33][34]. As well as result was consistent since the first registry in the eastern province for Saudi women [35] which mentioned that the crude incidence rate (CIR), age-standardized incidence rate (ASR) were 43.6 and 95.5, correspondingly. In another study in eastern region between 1985-1995, they also found that most of the females were pre-menopausal (79%) at age below 50 years [15].…”
Section: Discussionsupporting
confidence: 50%
“…[6] In the UK lung cancer is still among the most frequently occurring cancers and accounts for one in five of new cancer cases; that is 34,000 new patients annually. [1011] In KSA, in contrast to early studies where lung cancer was rarely reported,[1221] the prevalence of lung cancer has increased significantly in the recent years; this is, mainly attributed to the increased incidence of cigarette smoking among men and women in our community. [22] In 2004, the National Cancer Registry in KSA reported that lung cancer ranked fifth in males and seventeenth in females.…”
mentioning
confidence: 99%
“…10 The incidence rate of cancer in Saudi Arabia is predicted to continue rising, partly due to rapid changes in lifestyle, the increasing consumption of cigarettes, the high caloric and fatty diet intake observed during the last decade, and partly due to the natural aging of this young Saudi population in the years to come. 11 …”
mentioning
confidence: 99%
“…Currently, lectures in a major hospital in Riyadh that foster public awareness of breast cancer are given every two months and certified nurses provide workshops on breast-examination. 11 Breast cancer awareness programs (BCAP) are meant to help in the prevention and early detection of breast cancer. This study was carried out with the objectives of (i) assessing the knowledge of breast cancer and its associated factors (risk and protective) among the women of Riyadh city, (ii) assessing the source of knowledge of breast cancer, (iii) observing any association between family history of breast cancer, marital status and educational level of study participants versus their knowledge and practice of breast self examination and mammography.…”
mentioning
confidence: 99%